Ekonomiczna analiza konstytucji Nowej Zelandii. Zarys problemu - Siekiera, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article is an attempt to look at the New Zealand constitution from the Law and Economics perspective. This methodological approach is relatively new and till now, insufficiently explored. It implies the rational choice of a human being who strives to maximize own usefulness in public life.This assumption requires the legal frameworks though. The South Pacific legal studies are indeed a scientific gap in Poland and the whole Europe. Due to this fact, it needs to be filled, by researching the law of the Oceanian states. The Constitution Act is de iure the source of legal values within the society. However, New Zealand, as the rest of the postcolonial states of the British Empire, does not possess a typical constitution according to the continental doctrine. The Constitution of New Zealand is compounded of many acts and customs of different hierarchy and origin. Law and EconoThis assumption requires the legal frameworks though. The South Pacific legal studies are indeed mics perspective allows also to analyse the constitutional law from the perspective of the pragmatic choices of citizens.
Keywords: prawo i ekonomia; prawo konstytucyjne; analiza konstytucji; konstytucja Nowej Zelandii; Nowa Zelandia